Psychological distress, job satisfaction, and work engagement among Palestinian teachers: a cross-sectional study. (March 2019) - Pepe, Alessandro; Addimando, Loredana; Dagdukee, Jamal; Veronese, Guido
Abstract: Background: Work engagement is a positive, fulfilling affective and motivational state of work-related wellbeing and a protective factor for workers' mental health. The aim of the present study was to examine the association between psychological distress (conceptualised as the target variable), job satisfaction, and work engagement in contexts of low-intensity warfare and political violence. According to the salutogenic perspective, the relationship between job satisfaction and psychological distress is influenced by the level of work engagement. Methods: We selected a convenience sample of 380 Palestinian teachers from Gaza (40%, 152 out of 380) and the West Bank (60%, 228 out of 380). The participants were recruited on-site during morning breaks from the classroom teaching activity. The selection criteria were being in a teaching position, and working in a primary or lower secondary school. The participants completed the Arabic versions of the Teacher Job satisfaction Scale (TJSS-9), the General Health Questionnaire (GHQ-12) and the Utrecht Work Engagement Scale (UWE-SF). The statistical strategy was based on structural equation modelling. The study was approved by the Ethical Board of the University of Milano Bicocca. Informed written consent was obtained from all participants. Findings: The General Health Questionnaire cumulative score revealed a medium to high level of psychological distress (mean 18·68 [SD 4·03]) among teachers, but high job satisfaction (mean 27·18 [SD 5·65]). The structural model showed an excellent fit (χ 2 (23)=69·6, p<0·0001, NC=3·021, NFI=0·939, NNFI=0·959, CFI=0·958, RMSEA=0·073). Job satisfaction and psychological distress had a moderate and inverse relationship that was, statistically speaking, fully mediated by the level of work engagement (F=17·05, p<0·001, R 2 =0·16). The direct effect of job satisfaction on work engagement was positive and medium (according to Cohen, 1988) in strength. Interpretation: The main finding of the study is that work engagement may mediate the impact of job satisfaction on teachers' psychological distress by lessening the effect of difficult working conditions. It further suggests that in order to mediate the effect of low job satisfaction on psychological distress of teachers, organisational policies and practices should focus on improving employees' work engagement. This means that, in developing job programmes for teachers in contexts characterised by difficult working conditions, the main focus must be to increase the level of subjective resources (eg, inner states, emotional activation, personal motivational processes) and workers' engagement rather than focusing primarily on job satisfaction. Funding: None.